Dietary Palygorskite Clay-Adsorbed Nano-ZnO Supplementation Improves the Intestinal Barrier Function of Weanling Pigs - Yu, Lihuai; Liu, Jun; Mao, Junzhou; Peng, Zhong; Zhong, Zhaoxing; Wang, Hongrong; Dong, Li (Frontiers in Nutrition, 2022)
This study aimed to investigate the effects of PNZ on intestinal mucosal barrier function in weaning piglets. A total of 210 21-day-old piglets with similar body weights (6.30 ± 0.51 kg) were randomly allocated into 7 groups: control group (CON), antibiotic group (ANT), ZnO group (ZO), nano-ZnO group (NZO) and low, middle and high PNZ groups (LPNZ, MPNZ, HPNZ). The seven groups were respectively fed control diets or control diets supplemented with antibiotics; 3,000 mg/kg ZnO; 800 mg/kg nano-ZnO; 700, 1 000, or 1 300 mg/kg PNZ. More integrated intestinal villi were observed in the LPNZ. The crypt depth of the jejunum (P<0.05) in the LPNZ was significantly decreased compared to that of the CON, ANT and NZO. The LPNZ had a greater ratio of villus height to crypt depth (V/C) in the jejunum (P<0.05) than the CON and NZO. In addition, the villus width and surface area of the ileum were significantly increased in the ZO and LPNZ compared to ANT and NZO (P<0.05). Compared with the CON and ANT, the number of goblet cells in the mucosa of the jejunum and ileum in the PNZ was increased (P<0.05). The contents of TNF-α and IL-1β in the jejunal mucosa of the LPNZ were lower than the ANT and NZO (P<0.05). Compared with the other groups, the contents of sIgA in the jejunal mucosa of the LPNZ were significantly increased (P<0.05). The contents of IL-4 were greater in the ileal mucosa of the LPNZ than in the ANT, ZO and NZO (P<0.05). For the mRNA expression, the MPNZ decreased the TNF-α compared with the CON (P<0.05). The MUC2 was significantly increased in the mucosa of the jejunum and ileum in the LPNZ compared to the ANT and NZO (P<0.05). Compared with the other groups, the ZO1 in the jejunal mucosa of the LPNZ was significantly increased (P<0.05). In the ileum, the TLR4 and MyD88 was downregulated in MPNZ compared with NZO (P<0.05). In conclusion, supplementation with PNZ could effectively improve the intestinal barrier function of weanling piglets and potentially could replace the use of high doses of ZnO and antibiotics.